Pengembangan Lembar Kerja Siswa (LKS) Fisika Berbasis Problem Based Learning Untuk Meningkatkan Kemampuan Pemecahan Masalah - Choeriyah, Hidayatul; Yulianti, Dwi; Yulianti, Ian (UPEJ Unnes Physics Education Journal, 2021)
The goals of this research are to identify the characteristics of Problem Based Learning-based student worksheets, determine the feasibility level of Problem Based Learning-based student worksheets, determine the increase in student cognitive learning outcomes, and determine the increase in student problem-solving abilities. The method of this research is Research and Development (R&D) with One Group Pretest-Posttest Design. The results of the feasibility test from the validator and the results of the readability test showed that the Problem Based Learning-based student worksheets are very suitable for use in physics learning and this is easy to understand. The use of student worksheets in learning can increase students cognitive learning outcomes and students problem solving abilities.